Characterization of glomalin proteins in soil: A potential indicator of erosion intensity - Jović Branislav; Lukić Tin; Jović Danica; Radnović Nikola; Schaetzl Randall J.; Marković Slobodan B. (Open Geosciences)
In this study, in a pioneering effort, glomalin proteins were extracted and geochemically characterized from soil in Serbia. Standard chemical (dry combustion, Walkley-Black) and spectroscopic methods (fourier transform infrared spectroscopy (FTIR), dynamic light scattering (DLS), scanning electron microscope (SEM)) were used to gain insight into the glomalin proteins. Samples from the City of Novi Sad (Serbia) were used for characterization and comparison. The soil contained an average of 17 mg/g of glomalin, representing ≈21% of the soil organic matter. DLS zeta potential analysis and the FTIR spectra reveal two significant differences before and after glomalin extraction, indicating a relationship between sand fractions and organic matter that affects particle aggregation and erosion potential. A comparison of SEM images and DLS results reveals that the glomalin extract consists of two particle size groups (0.08–1 and 6 µm), suggesting that the extraction process isolates only a smaller fraction of proteins and less tightly bound particles, indicating that soil aggregation is influenced by both mineralogy and the characteristics of organic matter. Hence, our research raises important questions about the role of glomalin in mitigating soil degradation processes, particularly soil erosion. Our study will enhance the overall understanding of glomalin, inspire future research, and prove beneficial for the sustainable restoration of degraded lands.